Papaya—I - Cabrera Mederos, Dariel (2023)
This chapter reviews the viruses that have been reported infecting papaya (Carica papaya L.) worldwide, focusing on papaya mosaic, papaya leaf distortion mosaic, papaya apical necrosis, and papaya leaf curl diseases. These diseases are responsible for serious losses of crop quality and production throughout the world; some aspects such as distribution, etiology, and epidemiology are discussed.